Constellations - Todd, Michael, author; Steensen, Sasha, advisor; Lehene, Marius, committee member; Candelaria Fletcher, Harrison, committee member (Colorado State University. Libraries, 2023)
Constellations is a researched book-length lyric essay concerning notions of faith and belief weighed against science and the bodily experience, of layers of meaning, of personal truth. The piece takes the form of "constellations" of text in place of stars. The text appears on 4x6" cards against a black background with speckled white to indicate "space"; white lines suggest an assembly which corresponds to a map with instructions. However, the same instructions encourage user agency in how to assemble and navigate the work—flipping through the cards in a numbered sequence, or in a random sequence, or assembling them according to the map, or assembling them as they, the audience, see fit.